Last quarter. 1 - Yazawa, Ai, 1967-; Greenway, Max (VIZ Media, LLC, 2024)
After her father remarries, Mizuki struggles to adapt to life with a new mother and sister. She meets a blue-eyed man named Adam in Shibuya and is instantly drawn to him. Years later, after a brush with death, a young girl named Hotaru meets Mizuki in a dream. The next day, while searching for her cat, Hotaru wanders into an abandon mansion and sees a mysterious girl playing a piano. Hotaru and her friends return, but only Hotaru can see her. The group becomes determined to uncover her identity and why she has appeared.